The in-between : unforgettable encounters during life's final moments - Vlahos, Hadley (Ballantine Books, 2023)
"Passionate advocate for end-of-life care and TikTok star Nurse Hadley shares moving stories of joy, wisdom, and redemption from her patients' final moments, offering powerful lessons on facing death, recovering from loss, and how to live your life in this deeply personal memoir. Talking about death and dying is considered taboo in popular culture, even in the medical field. Our understanding of death is riddled with misconceptions: memories flashing before our eyes, cascading regrets, and chasing bright lights at the end of tunnels. But for most people, this will not be their experience. Rather, it will be a slower process requiring preparedness, good humor, and a bit of faith. At the forefront of changing attitudes around palliative care is TikTok personality Hadley Vlahos, whose videos collect and share the heartbreaking, remarkable, and uplifting stories of her patients. Vlahos was raised in a strict religious household, but began questioning her beliefs after she got pregnant at nineteen and was shunned by her community. A single mother on welfare, she went to nursing school with the sole purpose of keeping a roof over her and her son's head. Soon, however, nursing became more than a job, and she found her calling in palliative care and hospice work. Now, Vlahos is changing the conversation around death, showing that end-of-life care can teach us just as much about how to live as it does about how we die. In The In-Between, Vlahos recounts the most impactful stories from the people she's worked with-from the woman struggling with her religious beliefs despite her strict Catholic upbringing, to the older man seeing visions of his late daughter, to the young patient who laments that she spent so much of her short life worrying about what others thought of her-while also sharing her own fascinating journey. With profound insight, humility, and respect, The In-Between is a heart-rending memoir about how caring for others can transform a life, while also offering wisdom and comfort for those dealing with loss and providing inspiration for how to live now"--